Digital Innovation in Arabic Language Learning Models for Islamic Higher Education - Wahyuni, Imelda; Zulaeha; Budiarti; Nasiru, LM Akramullah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study aims to examine the innovation of digital-based Arabic learning models, particularly regarding Human Resource (HR) innovations and the utilization of digital facilities at three Islamic Higher Education (Perguruan Tinggi Keagamaan Islam/PTKI) Institutions in Southeast Sulawesi. This qualitative research employs a phenomenological approach, with data collected from primary and secondary sources through observation, interviews, Focus Group Discussions (FGD), and document studies. The data was analyzed using categorization, description, and synthesis techniques, with data validity tested through triangulation. The findings of this article indicate that the State Islamic Institute (IAIN) Kendari, the Islamic College (STAI) YPIQ Baubau, and the Islamic Institute (IAI) Al-Mawaddah Warahmah Kolaka have implemented innovations in digital-based Arabic learning models. The creativity of human resources (lecturers, students, and administrative staff) shows different adaptation styles in utilizing digital facilities. These innovations have facilitated Arabic language learning but have not been fully supported by the digital competence of human resources at these three institutions. In terms of digital facilities meeting standard requirements, the three Islamic Higher Education Institutions exhibit varying levels of innovation in digital-based Arabic learning models, especially in operational digital formats, HR competence readiness, and availability of facilities. The digital-based Arabic learning model innovations at these institutions offer advantages, compatibility, and religious complexity. These innovations are implemented with a commitment to enhancing HR creativity and providing representative digital facilities based on needs.